Discordant Elastography Images of Breast Lesions: How Various Factors Lead to Discordant Findings - Yoon, J. H.; Kim, M. J.; Kim, E.-K.; Moon, H. J.; Choi, J. S. (Ultraschall in der Medizin - European Journal of Ultrasound, 2013)
Purpose: To evaluate the rate of the elastography-pathology discordance, and evaluate which various factors have an effect on discordant elastography images (DEI) of breast lesions. Materials and Methods: Elastography images of 284 pathologically confirmed breast lesions of 233 patients were evaluated. Elasticity scores were compared to pathology results, and lesions were divided into 4 groups: benign concordant/discordant, and malignant concordant/discordant. The rate of DEI among benign and malignant lesions was calculated and compared. Patient, lesion factors and image adequacy were compared among the concordant and discordant groups for analysis. Results: Among the 284 breast lesions, 225 (79.2 %) were benign, and 59 (20.8 %) were malignant. The rate of DEI among malignant lesions was significantly higher than in benign lesions, i. e., 52.5 vs. 3.1 % (p < 0.001). Discordant images were more significantly seen in patients with extremely dense breasts on mammography in benign lesions, 42.9 vs. 11.9 % (p = 0.034). Discordant images were more significantly seen in malignant lesions < 10 mm or ≥ 20 mm (p = 0.006), and those with inadequate images (64.5 vs. 35.5 %, p < 0.001). Conclusion: The rate of DEI was higher in malignant lesions than in benign lesions. Dense breast parenchyma, lesion size and image adequacy showed significance in discordant images of elastography which need consideration in image acquisition and interpretation.
Keywords: breast; ultrasound; neoplasms